The soul of the sick - Delgado, Honorio (1957)
The medicine was originally essentially soul by its aim and the means employed. Indeed, both the man and pre-medical practitioner, there is the beginning of all cultures regard to physician-priest of the pre-Hippocratic Greek civilization, the disease is evil soul and its treatment appeals to intangible powers : of brujesca way among savages, cultural and moral way of temples dedicated to Apollo, god Serapis and, above all, Esculapius.